2022
DOI: 10.3389/fimmu.2022.812431
|View full text |Cite
|
Sign up to set email alerts
|

Functional Roles of Chemokine Receptor CCR2 and Its Ligands in Liver Disease

Abstract: Chemokines are a family of cytokines that orchestrate the migration and positioning of immune cells within tissues and are critical for the function of the immune system. CCR2 participates in liver pathology, including acute liver injury, chronic hepatitis, fibrosis/cirrhosis, and tumor progression, by mediating the recruitment of immune cells to inflammation and tumor sites. Although a variety of chemokines have been well studied in various diseases, there is no comprehensive review presenting the roles of al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 153 publications
(243 reference statements)
1
36
0
Order By: Relevance
“…Experiments in mice indicate that the development of cirrhosis can actually be delayed by CCL16 via the inhibition of hepatic stellate cells, suggesting that this chemokine may exert a unique disease-limiting role in the liver [ 69 ]. Notably, a recent evaluation of a large number of HCC samples confirmed that mean CCL16 mRNA levels were essentially unchanged with respect to non-tumour tissue, but also revealed a low-populated tail of the distribution extending towards very high figures, which was not observed in the reference group [ 70 ]. These samples may reflect cases with more significant local inflammation, possibly leading to CCL16 induction in non-hepatocytes, or with overproduction by the tumour cells themselves; our HBV-related tumour cohort featuring a lower number of specimens with a single outlier ( Figure 2 ) may actually be sampling the same underlying distribution.…”
Section: Resultsmentioning
confidence: 99%
“…Experiments in mice indicate that the development of cirrhosis can actually be delayed by CCL16 via the inhibition of hepatic stellate cells, suggesting that this chemokine may exert a unique disease-limiting role in the liver [ 69 ]. Notably, a recent evaluation of a large number of HCC samples confirmed that mean CCL16 mRNA levels were essentially unchanged with respect to non-tumour tissue, but also revealed a low-populated tail of the distribution extending towards very high figures, which was not observed in the reference group [ 70 ]. These samples may reflect cases with more significant local inflammation, possibly leading to CCL16 induction in non-hepatocytes, or with overproduction by the tumour cells themselves; our HBV-related tumour cohort featuring a lower number of specimens with a single outlier ( Figure 2 ) may actually be sampling the same underlying distribution.…”
Section: Resultsmentioning
confidence: 99%
“…CCR2 regulated the migration and positioning of immune cells within tissues were critical for the function of the immune system. CCR2 participated in liver pathology, including acute liver injury (ALI), chronic hepatitis, brosis/cirrhosis, and tumor progression, by mediating the recruitment of immune cells to in ammation and tumor sites [17]. CCR2 de ciency reduced brosis and CCR2 was required for recruitment of hepatic macrophages [18].…”
Section: Discussionmentioning
confidence: 99%
“…CCL13, or monocyte chemoattract protein-4 (MCP-4), is a molecule that induces chemotaxis in monocytes⁄macrophages, T lymphocytes, and eosinophils by binding cell surface chemokine receptors such as CCR2, CCR3, and CCR5 [ 170 ]. It also plays an important role in different cell functions, including migration, invasion, motility, and proliferation [ 170 ]. Two different studies measured circulating CCL13 levels in SSc patients [ 171 , 172 ].…”
Section: Cytokinesmentioning
confidence: 99%